Macular configuration determined by optical coherence tomography after idiopathic macular hole surgery with or without internal limiting membrane peeling. Issue 11 (1st November 2002) - Uemoto, R; Yamamoto, S; Aoki, T; Tsukahara, I; Yamamoto, T; Takeuchi, S
Abstract : Aims: To evaluate the effect of pars plana vitrectomy (PPV) with or without internal limiting membrane (ILM) peeling on the closure and configuration of idiopathic macular holes (IMH). Methods: PPV was performed for IMH on 44 eyes with ILM peeling (ILM peeled group) and on 42 eyes without ILM removal (ILM preserved group). Optical coherence tomography (OCT) was performed on 34 ILM peeled eyes and 14 ILM preserved eyes after successful surgery. The repaired macular holes were classified by the OCT images as being of "good shape" (nearly normal foveal contour) or "poor shape" (abnormal foveal contour with flat fovea and steep edge, or with a thick retina without a foveal pit). Results: The anatomical closure rate was significantly higher in the ILM peeled group (93.2%) than in the ILM preserved group (76.2%) (p = 0.028). In the ILM peeled group, 31 eyes had a fovea of good shape and three eyes had a fovea with a poor shape, while in the ILM preserved group, six eyes had a fovea of good shape and eight eyes had a fovea of poor shape. The percentage of eyes with good macular configuration in the ILM peeled group was significantly higher than in the ILM preserved group (p = 0.0003). No significant difference was found in the postoperative visual acuity and the increase of visual acuity between the ILM peeled group and the ILM preserved group (p = 0.26, and p = 0.91 respectively). There was also no significant difference in the postoperative visual acuity and improvement in visual acuity between eyes with a fovea of good shape and those with fovea of poor shape fovea (p = 0.99 and p = 0.66, respectively). Conclusions: ILM peeling may provide better anatomical success and recovery of the macular shape, but the postoperative visual acuity and improvement of visual acuity were not related to the morphological results.